Feminist Pedagogies and Graduate Adult and Higher Education for Women Students: Matters of Connection and Possibility - Andre P. Grace (Adult Education Research Conference, 2000)
This essay examines the disconnection between the homeplace and the university in graduate education for women students. It explores the ways that positional models of feminist pedagogies can be used to develop more inclusive and transformative forms of graduate education.